The Elite Deliberative Democratic Model in The Public Policy Formulation for Madrasah Diniyyah (Islamic Non Formal School) Development in East Java, Indonesia - Ismail, Ismail; Wardi, Moh (Nadwa: Jurnal Pendidikan Islam, 2019)
This research intend to discuss about public policy from East Java province government to improve the quality of Islamic religious education. The results of this study were: (1) East Java Provincial Government used policy formulation model in the name "elite deliberative democratic ". A policy formulation model that combines several theories of policy formulation, there are elite, deliberative theory, and democratic theory. (2) The policy formulation was done through several stages: They are reading of the reality; preparation of the general policy of long-term development; arrangement of short-term development policy; the preparation and stipulation of Regional Regulations, and the Governor Regulation on Translation of APBD; (3). The government of East Java province has under graduate Scholarship program (S.1) for Madrasah diniyyah teachers.Â AbstrakPenelitian ini bermaksud membahas tentang kebijakan publik dari pemerintah provinsi Jawa Timur untuk meningkatkan kualitas pendidikan agama Islam. Hasil penelitian ini adalah: (1) Pemerintah Provinsi Jawa Timur menggunakan model perumusan kebijakan dengan nama "elite deliberative demokratis". Sebuah model perumusan kebijakan yang menggabungkan beberapa teori perumusan kebijakan, ada elit, teori deliberatif, dan teori demokrasi. (2) Perumusan kebijakan dilakukan melalui beberapa tahap: Mereka membaca realitas; persiapan kebijakan umum pembangunan jangka panjang; pengaturan kebijakan pembangunan jangka pendek; persiapan dan penetapan Peraturan Daerah, dan Peraturan Gubernur tentang Penerjemahan APBD; (3) Pemerintah provinsi Jawa Timur memiliki program sarjana (S.1) untuk guru Madrasah diniyyahÂ